2007
DOI: 10.4269/ajtmh.2007.77.636
|View full text |Cite
|
Sign up to set email alerts
|

Use of kDNA-based Polymerase Chain Reaction as a Sensitive and Differentially Diagnostic Method of American Tegumentary Leishmaniasis in Disease-Endemic Areas of Northern Argentina

Abstract: We evaluated the polymerase chain reaction (PCR) for the diagnosis of endemic American Tegumentary Leishmaniasis in Salta, Argentina. Diverse Leishmania species, coexistence of mycotic and varicose ulcers, and high endemicity T. cruzi, represent diagnostic challenges in the region. We performed a simplified PCR using sensitive, generic primers on samples obtained by a non-invasive method. We tested different culture types and clinical specimens with other microorganisms that induce leishmaniasis-like lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
1
19
1
2
Order By: Relevance
“…This species is reported to be the major causative agent of ML in Latin America; and it is estimated that 3-5% of CL patients progress to ML form when infected with this species 7 . The specificity of these specific primers for the Leishmania genus has been reported in previous studies and no cross-reaction was observed for paracoccidioidomycosis, histoplasmosis, cutaneous tuberculosis, and candidiasis 3 , squamous cell carcinoma, sporotrichosis, leprosy, lentigo, pyodermitis and vascular ulcer 17 .…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This species is reported to be the major causative agent of ML in Latin America; and it is estimated that 3-5% of CL patients progress to ML form when infected with this species 7 . The specificity of these specific primers for the Leishmania genus has been reported in previous studies and no cross-reaction was observed for paracoccidioidomycosis, histoplasmosis, cutaneous tuberculosis, and candidiasis 3 , squamous cell carcinoma, sporotrichosis, leprosy, lentigo, pyodermitis and vascular ulcer 17 .…”
Section: Introductionsupporting
confidence: 74%
“…Concerning the DI test, several studies have demonstrated that the quality of the prepared slides, the age of the lesions, the presence of secondary microorganisms 6 24 , and pre-treatment of the lesions can lead to atypical forms of the parasite 23 , resulting in a wide variation in the level of sensitivity of the DI tests ranging from 10% to 74.4% 3 4 5 11 15 17 . Corroborating this, we observed that 20 of the 29 samples presenting negative or suggestive results by DI test were positive when evaluated by kDNA-PCR (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…These factors indicate that the sensitivity of the diagnostic method should have the priority for maximization, rather than its specificity [17]. Previous PCR analyses for the diagnosis of leishmaniases displayed sensitivities ranging from 51.7% to 100% [18-20]. This wide variability in the sensitivity may very well be due to the methods employed, but also attributable to differences in the sampling techniques, or the clinical and laboratory criteria applied for defining the presence or absence of the disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…2 Other Leishmania spp., reacting with generic PCR primers, 25 circulate in the area and may infect dogs. 7,8 Moreover, in our comparative analysis (Table 1), parasitological methods displayed a very low sensitivity.…”
Section: Resultsmentioning
confidence: 99%